The Retranslation and Mediated Translation of Audiovisual Content in Multilingual Spain: Reasons and Market Trends - Chaume, Frederic (Status Quaestionis, 2019)
Retranslations are the second, third, fourth or nth-translations of the same text produced at a later stage. In the case of audiovisual content, retranslations occur under certain circumstances. Focusing on Spain as a multilingual country, where regional languages demand new translations, frequently conceived as mediated translations, this article concentrates on the definition of retranslation and the differences between retranslation and mediated translation, and also lists the major reasons why retranslations, be them redubbings or resubtitlings, are commissioned and carried about. Economic, historical, linguistic and political issues triggering retranslations will also be dealt with, and some translatological conclusions will be drawn, as well as some new avenues of research grounded on retranslations.